PERFORMING STANCE THROUGH MEMESPEAK IN SENATOR FATIMA PAYMAN’S PARLIAMENTARY SPEECH - Rizal Prasetyo, Bima (Language Horizon: Journal of Language Studies, 2025)
This study investigates how memespeak—a language register inspired by internet meme culture—is employed to perform communicative stance in a parliamentary speech by Australian Senator Fatima Payman. Using Du Bois’s (2007) stance triangle as an analytical framework, the research examines expressions like “goofy ahh government” and “sigma” to reveal how Payman evaluates political opponents, positions herself in relation to youth audiences, and aligns with digital subcultures. The findings show that memespeak functions as a rhetorical tool to build generational affinity and symbolic solidarity, while challenging conventional norms of political discourse.